2017
DOI: 10.3766/jaaa.15130
|View full text |Cite
|
Sign up to set email alerts
|

Children Diagnosed with Auditory Processing Disorder and Their Parents: A Qualitative Study about Perceptions of Living with APD

Abstract: The three themes identified in this research provide a novel understanding of the experience of APD. The themes reflect the psychosocial consequences of external factors that are created internally through "thought" and expressed externally through "behavior." Pathways to support positive coping strategies while discouraging negative coping strategies will enable children to overcome problems and improve their psychosocial well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Based on the Kuopio Ischaemic Heart Disease cohort recruited in eastern Finland, a long-term prospective cohort study has suggested that low serum magnesium levels are independently associated with increasing both the total risk of fracture and the femoral fracture risk in middle-aged Caucasian men ( Kunutsor et al., 2017 ). Using the method of meta-analysis and systematic reviews to evaluate the effects of magnesium supplementation on hypertension, a few studies have found that higher doses of magnesium lead to greater reductions in blood pressure ( Lawton et al., 2017 ; Volpe, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the Kuopio Ischaemic Heart Disease cohort recruited in eastern Finland, a long-term prospective cohort study has suggested that low serum magnesium levels are independently associated with increasing both the total risk of fracture and the femoral fracture risk in middle-aged Caucasian men ( Kunutsor et al., 2017 ). Using the method of meta-analysis and systematic reviews to evaluate the effects of magnesium supplementation on hypertension, a few studies have found that higher doses of magnesium lead to greater reductions in blood pressure ( Lawton et al., 2017 ; Volpe, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, studies have shown that lower scores in personality traits such as conscientiousness and emotional stability, compared to mothers of children with APD, may predispose them to parental burnout (Le Vigouroux, Scola, Raes, Mikolajczak, & Roskam, 2017)although agreeableness, which was at the same level in both groups, may play a protective role. Low conscientiousness and high neuroticism are also found in mothers of children with ADHD, which may possibly include mothers of children with APD, since symptoms in neurodevelopmental disorders tend to overlap (Ahmmed et al, 2014;de Wit et al, 2018;Lawton et al, 2017;Lewandowska et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Some of them may have problems with understanding prosody-related changes in a message's meaning. Summarizing, the difficulties they experience relate to auditory functioning and task-oriented activities that engage memory, attention, language, and reading (de Wit et al, 2018), and perhaps activities related to socialemotional functioning (Lawton et al, 2017;Rostkowska et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Academic skills affected are mostly in higher-order language like reading and spelling ( 18 ). External factors contributing to negative psychosocial well-being in children with APD are environmentally based issues and support dissatisfaction ( 19 ).…”
Section: Introductionmentioning
confidence: 99%